Legitimacy and Standard Development in Multi-Stakeholder Initiatives: A Case Study of the Leonardo Academy’s Sustainable Agriculture Standard Initiative - Hatanaka, Maki; Konefal, Jason (The International Journal of Sociology of Agriculture and Food, 2013)
Non-state, market-driven forms of governance, especially those that use multi-stakeholder initiatives (MSIs), have become a prominent mechanism for regulating food and agriculture. While the standards generated by MSIs and their implementation have been studied widely, the internal practices of MSIs have received less attention. This article addresses this research gap using a case study of the Leonardo Academy’s sustainable agriculture standard initiative. Specifically, the focus is on the relationship between the standard-development process and legitimacy. Using a framework that conceptualizes legitimacy in MSIs as consisting of three interrelated processes – input, procedural, and output – we examine: 1. how the practices of the standard-development process affect the legitimacy of the Leonardo Academy’s sustainable agriculture standard initiative, and 2. how the quest for legitimacy affects the initiative. In conclusion, we contend that in- put, procedural, and output legitimacy may not always positively correlate, that legitimacy is best understood as relational, and that legitimacy in MSIs is per- formative.